Chick Early Amniotic Fluid Alleviates Dextran-Sulfate-Sodium-Induced Colitis in Mice via T-Cell Receptor Pathway - Fan Chen; Yining Zhao; Yanfa Dai; Ning Sun; Xuezheng Gao; Jiajun Yin; Zhenhe Zhou; Ke-jia Wu (Antioxidants)
Ulcerative colitis (UC) is a chronic immune disease that is difficult to cure. We recently found that chick early amniotic fluid (ceAF) has notable anti-inflammatory and antioxidative properties, through its active components. This study demonstrates the potential of ceAF as a protective agent against UC. UPLC-MS mass spectrometry identified key components of ceAF, including various fatty acids and nucleosides. In vitro, ceAF improved viability in DSS-induced Caco-2 cells, reduced pro-inflammatory cytokines IL-1β and TNF-α, and increased the anti-inflammatory cytokine IL-10. It also upregulated the tight junction proteins ZO-1 and occludin. In DSS-induced UC mice, ceAF treatment alleviated weight loss, colon shortening, and disease activity, while improving histopathology, crypt depth, and colonic fibrosis. Mechanistically, ceAF’s anti-inflammatory effects are mediated by inhibiting the overactivation of TCR signaling through the LCK/ZAP70/LAT pathway. Our findings suggest that ceAF could be a valuable nutritional intervention for UC, potentially enhancing existing functional foods aimed at managing this condition.